SISTEM INFORMASI AKUNTANSI PENJUALAN BARANG DAN PENDAPATAN DI BUMDES BERBASIS WEB DENGAN METODE FIFO (First-In, First-Out) - Sagara, Frans; Kusumajaya, Robby Andika; Santoso, Agustinus Budi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to design and develop a web-based accounting information system for sales and revenue management at BUMDes Estu Dadi Mulyo using the First-In, First-Out (FIFO) method. The primary issue identified was the absence of an integrated system to manage sales transactions, cost of goods sold (COGS) calculations, and financial reporting efficiently. The research employed a Research and Development (R&D) methodology, consisting of six stages: problem identification, data collection, system design, prototype development, validation, and product testing. The system was developed using PHP and MySQL database. The findings indicate that the proposed system improves transaction management, streamlines monthly reporting, and enhances the accuracy of COGS calculations. However, the system is limited to internal use within BUMDes and features a relatively simple user interface. Future research should focus on improving interface design and implementing robust data security features.